RILEM TC 277-LHS REPORT - Alvarez, José Ignacio (2022)
The main objective of RILEM TC LHS-277 “Specifications for testing and evaluation of lime-based repair materials for historic Structures” is the revision, adaption and, when necessary proposal, of the test methods to accurately study lime-based binding systems and mixtures, such as mortars and grouts. The empiric use of the lime-based composites and the predominant employ of cement in the field of Civil Engineering have led to the widespread application of test methods developed for cement-based composites to test the former. However, the clear differences in composition and performance between modern cement binders and lime-based materials would advise to explore specific test methods for the latter. To undertake this task the previous knowledge on the mechanisms of setting and hardening of these binders must be revised, arranged and synthesized. Processes such as drying, carbonation, hydration and pozzolanic reaction may occur during the setting and hardening of lime-based mortars and competition between them cannot be underestimated. With the aim of underpinning the revision and proposal of test methods for lime-based systems, this review paper reports a comprehensive study of the mechanisms of setting and hardening of these binders, considering the variability of the composition, which includes pure air lime as well as lime with hydraulic properties, lime-cement and lime-pozzolan systems.